Clinical application of fetal genome-wide sequencing during pregnancy: position statement of the Canadian College of Medical Geneticists. Issue 10 (20th September 2021) - Lazier, Joanna; Hartley, Taila; Brock, Jo-Ann; Caluseriu, Oana; Chitayat, David; Laberge, Anne-Marie; Langlois, Sylvie; Lauzon, Julie; Nelson, Tanya N; Parboosingh, Jillian; Stavropoulos, Dimitri J; Boycott, Kym; et al.
Abstract : Purpose and scope: The aim of this position statement is to provide recommendations for Canadian healthcare professionals regarding the use of genome-wide sequencing (GWS) in the context of diagnostic testing of the fetus during pregnancy. This statement was developed to facilitate clinical translation of GWS as a prenatal diagnostic test and the development of best practices in Canada, but the applicability of this document is broader and aims to help professionals in other healthcare systems. Methods of statement development: A multidisciplinary group was assembled to review existing literature on fetal GWS for genetic diagnosis in the context of suspected monogenic diseases and to make recommendations relevant to the Canadian context. The statement was circulated for comments to the Canadian College of Medical Geneticists (CCMG) membership-at-large and, following incorporation of feedback, approved by the CCMG Board of Directors on 19 February 2021. Results and conclusions: The use of prenatal GWS is indicated for the investigation of multiple fetal anomalies. Its use in the context of isolated fetal anomaly should be guided by available resources and current evidence, which is continually changing. During pregnancy, GWS should be ordered by, or in collaboration with, a medical geneticist. It should be used following detailed phenotyping to interrogate known disease genes, preferably using a trio approach, following detailed fetal phenotyping. Testing should be done with an overall aim to help in the management of the pregnancy, delivery and postnatal care. It should be guided by personal utility of the test for the pregnant person and clinical utility for pregnancy and birth management, as outlined herein. Genetic counselling is crucial in making the parental decision an informed decision. Chromosomal microarray analysis should be completed in parallel or prior to GWS and should be preceded by Quantitative Fluorescent PCR (QF-PCR) for detection of common aneuploidies. In normal circumstances, only pathogenic and likely pathogenic variants with a high likelihood of being associated with the identified fetal anomalies should be reported. Reporting of secondary findings, defined as purposeful analysis of variants in a set of medically actionable genes, should not, by default, be performed in the prenatal context. Laboratories should only report incidental findings that reveal risk of a significant Mendelian condition during infancy and childhood. Should a laboratory have a policy for reporting incidental findings in medically actionable adult-onset conditions, they should only be reported with explicit opt-in consent signed by the tested individuals. Genetic counselling is crucial in disclosing the test results and the implications the results may have for the fetus. It should be emphasised that negative results do not rule out a genetic diagnosis nor guarantee a good prognosis. Postnatal phenotyping and reanalysis of existing data should be considered. Families should be given the opportunity to participate in research studies as appropriate. These recommendations will be routinely re-evaluated as knowledge of the diagnostic and clinical utility of fetal GWS during pregnancy improves.